Hypertriglyceridaemia as a risk factor for critical care admission in acute pancreatitis: A prospective study. (October 2020) - Adiamah, Alfred; Kushairi, Anisa; Tumilty, Sue; Na, Yuuki; Crook, Martin; Brooks, Adam J.; Lobo, Dileep N.; ,; Alabraba, E.; Beckingham, I.J.; Cameron, I.C.; Gomez, D.; et al.
Summary: Background and aims: Hypertriglyceridaemia is both a primary cause of acute pancreatitis and an epiphenomenon. This study aimed to define the associations between hypertriglyceridaemia and clinical outcomes in patients admitted with acute pancreatitis. Methods: This single-centre prospective observational study included patients with a confirmed clinical, biochemical or radiological diagnosis of acute pancreatitis from August 2017 to September 2018. Baseline demographics, aetiology of pancreatitis, and fasting triglyceride concentrations were recorded and assessed against the surrogate markers of severity: admission to critical care, length of stay (LOS), readmission to hospital, and mortality. Results: In total, 304 patients with a mean ± SD age of 56.1 ± 19.7 years met the inclusion criteria. There were 217 (71.4%) patients with normotriglyceridaemia (<150 mg/dL or <1.7 mmol/L), 47 (15.5%) with mild hypertriglyceridaemia (150–199 mg/dL or 1.7–2.25 mmol/L) and 40 (13.2%) with moderate-to-severe hypertriglyceridaemia (≥200 mg/dL or >2.25 mmol/L). The underlying aetiologies of acute pancreatitis were gallstones (55%), alcohol (18%), idiopathic (15%), hypertriglyceridaemia (9%), iatrogenic (2%) and bile duct abnormalities (1%). Patients with hypertriglyceridaemia were younger than those with normotriglyceridaemia (p < 0.05). On multivariate regression, moderate-to-severe hypertriglyceridaemia (OR 5.66, 95% CI: 1.87 to 17.19, p = 0.002) and an elevated C-reactive protein concentration ≥120 mg/L (OR 1.00, 95% CI: 1.00–1.01, p = 0.040) were associated with admission to critical care. Moderate-to-severe hypertriglyceridaemia was also associated with an increased LOS (p = 0.002) but not readmission (p = 0.752) or mortality (p = 0.069). Conclusion: Moderate-to-severe hypertriglyceridaemia in all aetiological causes of acute pancreatitis was predictive of admission to critical care and prolonged LOS but not readmission or mortality.